The Popes as guardians of human dignity - Müller, Gerhard Ludwig (Chrześcijaństwo-Świat-Polityka, 2023)
The text emphasizes the significance of a Christian philosophy of life in guiding a society towards human rights and the dignity of individuals. It underscores the Church’s prophetic role, asserting that followers of Christ are called to uphold justice and oppose oppression. The text also highlights the interconnectedness of eternal salvation and temporal well-being, rooted in core Christian convictions. It explores the Church’s responsibility for the common good and the autonomy of earthly realities, advocating for the respectful stewardship of creation. The text addresses the contemporary challenge of protecting human life at all stages and emphasizes the Church’s historical commitment to the value of every individual. Drawing on Pope John Paul II and Pope Benedict XVI’s encyclicals, it asserts that the Church is inherently charitable and actively engaged in promoting human development, education, and well-being. The text rejects the notion that the Church should merely react to global issues, arguing for a proactive role in shaping the future by emphasizing humanity’s vocation within God’s creation. It critiques ideological pluralism that rejects moral truths, highlighting the emptiness and lack of true hope in a worldview without God. The text asserts that the Church’s antidote to this vision is to focus on the beauty and dignity of the human person, emphasizing the individual’s dual nature of soul and matter. It acknowledges the challenges within a secularized society but stresses the need for human rights to be rooted in an authority beyond human consensus for lasting universality.